Analysis of Flood Risks on The Power Distribution System Infrastructure at Pt PLN (Persero) Distribution Banten Due to Climate Change - Inez Carissa Abyati; Arie Dipareza Syafe’i (International Journal Labs, 2026)
The electricity distribution system in the work area of PT PLN (Persero) Banten Distribution Main Unit is facing increasing challenges due to the increasing frequency and intensity of floods affected by climate change. Historical data show that power outages due to natural disasters contribute significantly to the unreliability of distribution systems, with flood events occurring in seasonal patterns and tending to be spatially extensive. This condition requires a comprehensive understanding of the factors that cause flooding and the level of flood vulnerability in the area where the electricity infrastructure is located, as a basis for more targeted risk management efforts. This study uses a quantitative approach based on spatial analysis to identify and analyze flood vulnerability. Flood risk assessment is carried out by integrating four main parameters, namely slope slope, rainfall, land use, and soil type, each of which is weighted according to the level of influence on the occurrence of flooding. Rainfall data was analyzed using historical data for the period 2014–2024 as well as climate projections with the SSP 2-4.5 and SSP 5-8.5 Scenarios. All parameters are processed using the Geographic Information System (GIS) to produce flood vulnerability maps and identify the level of risk to the electricity infrastructure. The results showed that flood vulnerability in the study area was predominantly influenced by topographic factors, followed by soil type, while rainfall and land use had a relatively balanced level of influence. Flood risk mapping shows variations in vulnerability levels across different climate scenarios. In 2030, areas with the Vulnerable Risk and Moderately Vulnerable risk classes dominate, while in 2050 there will be a shift with the increasing dominance of Moderately Vulnerable Risk in both SSP scenarios. The integration of flood risk maps with infrastructure data shows that most distribution substations are located in medium to high flood risk zones, which confirms the importance of flood risk mapping as a basis for managing electricity infrastructure in vulnerable areas flooding.